2016
DOI: 10.1007/s12664-016-0653-0
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of graft steatosis after liver transplantation for cryptogenic cirrhosis in recently commenced liver transplant program

Abstract: Non-alcoholic fatty liver disease (NAFLD) seems to recur in at least one third of patients transplanted for non-alcoholic steatohepatitis (NASH)-related cirrhosis. While, NASH recurrence does not seem to affect overall graft and patient survival up to 10 years, cardiovascular and infection-related morbidity and mortality seem to be increased in these patients. This report looks at the graft histology in patients who were transplanted for NASH-related cirrhosis after short-term follow up. We report a high preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…A single-center retrospective study involving 696 patients with cirrhosis found only 13 (1.87%) patients had chronic hepatitis B infection [48]. In another study done on 81 patients with cirrhosis who were referred for liver transplantation, none had hepatitis B or C [49]. Even though nationwide data on prevalence of hepatitis C virus (HCV) in Sri Lanka is not available, studies conducted in various specific groups of population have shown a seroprevalence of <1% [46].…”
Section: Discussionmentioning
confidence: 99%
“…A single-center retrospective study involving 696 patients with cirrhosis found only 13 (1.87%) patients had chronic hepatitis B infection [48]. In another study done on 81 patients with cirrhosis who were referred for liver transplantation, none had hepatitis B or C [49]. Even though nationwide data on prevalence of hepatitis C virus (HCV) in Sri Lanka is not available, studies conducted in various specific groups of population have shown a seroprevalence of <1% [46].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary experience from Sri Lanka shows that NAFLD is one of the main reasons for rejecting potential donors of liver. 17 This is experienced at other liver transplant centers from the region as well. Nonalcoholic steatohepatitis is well recognized to recur in patients who undergo liver transplantation for cryptogenic cirrhosis.…”
Section: Introductionmentioning
confidence: 98%
“…However, they are more likely to die from cardiovascular diseases or sepsis (75). Recurrence of NASH in the graft following liver transplant is not uncommon (76).…”
Section: Liver Transplantationmentioning
confidence: 99%